The Core of the Curriculum for Accounting Majors (Book). - Burns, Thomas J.; Singer, Frank A. (The Accounting Review, 1980)
Abstract Reviews the book "The Core of the Curriculum for Accounting Majors," by Richard B. Flaherty.